Geração procedural de ambientes virtuais semânticos - Marson, Fernando Pinho (2012)
This work describes a computational model to generate semantic virtual environments procedurally, which can be used in games and behavioral simulations of crowds and groups of autonomous virtual agents. The process of creating environments, starts with a set of semantic information provided by the user. Such information are based on an abstract mental model, which describes relationships among the spaces that should be created. The proposed approach works in two different ways: building residential environments (i.e. houses and apartments) and also large environments. Large environments can be understood as complex virtual buildings, e.g., shopping malls, airports or train stations. For each type of environment is used a distinct method, more suitable to treat the specific environmental issues. After subdivide all spaces, the flow turns to become one again. As output we have geometry files and semantic description files that can be used in different applications as games and behavioral crowd simulations.